Transparent neutron shielding material with excellent radiation resistance and radiation protection system using same
The development of a radiation-resistant transparent neutron shielding material using a cured epoxy resin composition addresses the issue of transparency loss under gamma radiation, offering enhanced neutron shielding and radiation protection in high-risk environments.
Patent Information
- Application Number
- JP2020141927
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-08-25
- Publication Date
- 2025-04-10
- Estimated Expiration
- 2040-08-25
AI Technical Summary
Existing transparent neutron shielding materials lose transparency and effectiveness when exposed to high doses of gamma radiation, making them unsuitable for long-term use in radiation-intensive environments.
A radiation-resistant transparent neutron shielding material is developed using a cured epoxy resin composition with high hydrogen content, which maintains light transmittance and neutron shielding performance even after exposure to high doses of gamma radiation.
The material achieves superior neutron shielding performance compared to water, while minimizing coloration and maintaining transparency after irradiation, thus enhancing radiation protection in industries like nuclear power and medicine.
Smart Images

Figure 0007659750000003 
Figure 0007659750000004 
Figure 0007659750000005
Abstract
Description
[Technical field]
[0001] This invention relates to a neutron shielding material that is transparent and solid at room temperature and has excellent radiation resistance. [Background technology]
[0002] Radiation can be broadly divided into electromagnetic radiation and particle radiation. The main electromagnetic radiation is gamma rays and X-rays, while the main particle radiation is alpha rays (α rays = helium nuclei) and beta rays (β rays = electrons) that are produced by radioactive isotopes, and high-energy electrons, protons, neutrons, and heavy particles (heavy ions) that are produced in the space environment and accelerator facilities. Of these, neutrons, which are electrically neutral, cannot be blocked by matter due to electromagnetic interactions. Therefore, in order to protect the human body and other objects, shielding materials that are specifically tailored to the properties of neutrons will be required.
[0003] Neutrons are produced by nuclear fission in nuclear reactors, and continue to be produced by spontaneous nuclear fission and (α,n) reactions in spent nuclear fuel. They are also produced by high-energy particle nuclear reactions in particle accelerators used for medical and research purposes, and by photonuclear reactions (nuclear reactions between photons and atomic nuclei) in medical X-ray linacs with energies exceeding 20 million electron volts (20MeV). In addition to being related to various fields such as energy and medicine, neutrons are also used in industry for non-destructive testing and in medicine, such as cancer treatment.
[0004] When the human body is exposed to radiation, even at a dose of 1 Sv or less, where no immediate effects are seen, there are cases where probabilistic effects such as the development of cancer can occur, and since the existence of a threshold for these effects has not been confirmed, in work where radiation exposure is considered possible, it is necessary to keep the exposure dose as low as reasonably possible (As Low As Reasonably Achievable: ALARA). The most effective means of reducing radiation exposure during a certain work period in a limited space is to provide shielding.
[0005] High-energy neutrons penetrate deep into the human body and impart large amounts of energy to the elements that compose the human body, resulting in a large dose conversion factor that indicates the radiation risk to the human body, and thus having a significant impact on external exposure to the human body. Neutrons from medical accelerators, nuclear reactors, spent nuclear fuel, etc. are mainly generated in the energy range called fast neutrons, with kinetic energy of about one million electron volts (MeV). Therefore, efficient shielding of fast neutrons is highly effective in reducing external exposure to neutron radiation. It is known that deceleration by elastic scattering with hydrogen atoms, which have almost the same mass as neutrons, is effective in shielding fast neutrons, and materials with a high hydrogen content have been used as fast neutron shielding materials. Since neutrons are electrically neutral, thick shielding, i.e., a large amount of shielding material, is required to shield them, and shielding materials that are inexpensive and easy to handle are desired. Among inexpensive materials, hydrocarbon compounds with a relatively large number of hydrogen atoms (for example, paraffins, polyethylene resins), epoxy resins, acrylic resins, etc. are used and applied as neutron shielding structural members.
[0006] When neutrons are shielded with materials that contain hydrogen, the hydrogen captures thermal neutrons whose energy has dropped to thermal equilibrium, emitting gamma rays of 2.2 million electron volts (2.2 MeV). In addition, neutrons can be captured by various nuclides other than hydrogen and emit secondary gamma rays, so in order to shield neutrons and reduce radiation doses, gamma ray shielding is also required.
[0007] Spent fuel from nuclear power plants is shielded from neutrons and gamma rays by being submerged in pools of water several meters deep. Water has a high hydrogen content, so it has a high shielding effect, especially against neutrons.
[0008] For special shielding against neutrons, polyethylene is used, which is one of the solids with the highest hydrogen content, and polyethylene doped with boron is also used to suppress secondary gamma radiation production.
[0009] However, at thicknesses of 5 cm or more, which are significant as a neutron shield, it is difficult to maintain polyethylene transparency sufficient for use as a visual window. Water is transparent and contains a relatively large amount of hydrogen, so it has high neutron shielding performance, but since shielding materials often also function as structural materials, it is desirable for them to be solid in the temperature range in which they are used and to have a certain degree of strength. For this reason, it is often not practical to use water as a transparent neutron shield.
[0010] Transparent neutron shielding materials that have neutron shielding performance equal to or greater than that of water and are solid at room temperature are required in facilities that handle radioactive materials, nuclear power-related facilities, accelerator facilities, and other locations.
[0011] In the accident at the Fukushima Daiichi Nuclear Power Plant, which was caused by the tsunami resulting from the Tohoku Pacific Ocean Earthquake that occurred on March 11, 2011, the fuel in the three reactors melted down and became "fuel debris," which is now present inside and underground of the reactors. In order to safely proceed with the decommissioning of the Fukushima Daiichi Nuclear Power Plant, it is necessary to remove the fuel debris or analyze the removed debris. The fuel debris contains spontaneous fissionable nuclides such as 242Cm and 244Cm and alpha-ray emitting nuclides such as 238Pu, and neutrons generated by spontaneous fission and neutrons generated by the (alpha, n) reaction of alpha rays with light elements such as oxygen are emitted from the debris. When this fuel debris is removed from the reactor and analyzed, the external exposure of the workers to neutrons must be sufficiently reduced. The intensity of these neutrons is at a level that can cause high doses of radiation that are life-threatening, so they must be heavily shielded. The shape and composition of the fuel debris to be removed varies widely, and after the debris is removed from the containment vessel, it is possible that workers could carry out the removal operations while directly observing the debris in a simple cell installed outside the containment vessel. If such a cell had a window made of a transparent shielding material that can sufficiently block neutrons, the efficiency of the work would be significantly improved.
[0012] Space radiation, such as heavy ion particles contained in galactic cosmic rays (GCR) and energetic protons (e.g., captured in the Van Allen belts and from solar flares), provides significant radiation doses to workers, passengers, and equipment in the aerospace and other industries. For example, commercial high-altitude flights can expose airline crew and frequent flyers to radiation levels significantly above those permitted for the general public under legally recommended standards. High-energy heavy particles and protons react with the nuclei of atoms that make up the spacecraft's wall, generating neutron rays that are difficult to shield. Therefore, the aerospace industry also requires the development of more efficient neutron shielding materials. Transparent neutron shielding materials are particularly required for the windshields of high-altitude aircraft and the windows of spacecraft. Transparent neutron shielding materials are desirable for windows, which are closest to the crew.
[0013] Furthermore, in the medical field, "particle beam therapy" such as heavy ion cancer therapy and proton beam cancer therapy has become popular as a less invasive and highly effective cancer treatment method, but the use of these high-energy particles inevitably generates neutrons due to nuclear reactions between the particles and structural materials or the human body. X-ray linac therapy, which has been popular as a radiation cancer treatment method for a long time, has also developed to increase the energy of X-rays as the patient's body size increases, and as a result, the influence of neutrons generated by photonuclear reactions cannot be ignored. Furthermore, the technology of boron capture neutron therapy (BNCT), which directly uses neutrons to attack cancer cells, has also progressed significantly, such as by using neutrons from accelerators. For this reason, it is becoming increasingly necessary to simultaneously shield neutrons in future radiation medicine. In particular, transparent shielding materials are desired to reduce the exposure of medical staff while monitoring patients.
[0014] Among transparent materials, glass contains almost no hydrogen and therefore has extremely low neutron shielding performance. Acrylic resin has a lower neutron shielding performance than water because its hydrogen content is less than that of water.
[0015] From the above perspective, there is a demand for new neutron shielding materials that have higher neutron shielding performance and are transparent and solid at room temperature.
[0016] An example of such a neutron shielding material is the transparent neutron shielding material described in Patent Document 1. However, the inventors discovered a problem when they exposed the transparent neutron shielding body described in Patent Document 1 to an environment containing high doses of gamma rays, in that when irradiated with a dose of about 100 kGy, the transmittance decreased to 1 / 4 compared to when not irradiated, and when irradiated with 1 MGy, coloring was observed to the extent that transparency was impaired.
[0017] In hot cells that handle highly radioactive materials, the windows may be exposed to a radiation dose of about 10 kGy / h, which means that they will receive a radiation dose of about 100 kGy over several years of use. It is desirable for the windows to maintain a level of transparency that is practical even when exposed to such a large radiation dose.
[0018] Regarding transparent neutron shielding materials, Patent Document 1 discloses an epoxy resin neutron shielding material that has a light transmittance of 80% or more in the wavelength range of 400 nm to 700 nm and a thickness (1 / 10 valence layer) of 14 cm or less at which the dose of neutron rays generated by a Calfornium-252 point isotropic source is 1 / 10. Non-Patent Document 1 discusses the coloring of epoxy resin caused by irradiation with cobalt-60, and suggests the possibility of using it as a dosimeter in the range of 1-50 kGy by quantifying the coloring. When used as a shielding material, it is necessary to devise a way to reduce the coloring of the epoxy resin when used under radiation exposure.
[0019] To evaluate neutron shielding performance in radiation handling facilities, data on the attenuation of neutron and gamma ray doses in major shielding materials described in Non-Patent Document 2 is used. [Prior art documents] [Patent documents]
[0020] [Patent Document 1] WO2017213265A1 publication [Non-patent literature]
[0021] [Non-Patent Document 1] Nuclear Instruments and Methods in Physics Research B 311 (2013) 1-4 [Non-Patent Document 2] Nuclear Safety Technology Center, Public Interest Foundation, "Practical Shielding Calculation (Radiation) Data Collection for Radiation Facilities 2015" (October 2015)
[0022] Therefore, the inventors conducted research using the procedure described below to find a transparent neutron shielding material that does not lose its transparency even when exposed to an environment containing high doses of gamma rays. (1) Epoxy resin is a hydrogenated epoxy resin obtained by hydrogenating aromatic epoxy resin, and its high hydrogen content enhances neutron shielding performance.
[0023] (2) The epoxy resin selected in (1) is combined with an amine-based or acid anhydride-based hardener to select multiple combinations. (3) (2) Prepare a test piece measuring a few centimeters by a few centimeters by a few millimeters using the combination of epoxy resin and hardener selected in (2), and irradiate it using a cobalt-60 source to a dose of 100 kGy or 1 MGy.
[0024] (4) The visible light transmittance of the test piece before and after irradiation is measured using a tint meter or spectrophotometer. (5) For combinations that have a transmittance of 50% or more after 100 kGy irradiation, we will evaluate their neutron shielding performance by conducting shielding analysis using neutron transport calculations and shielding experiments using neutron sources such as americium-beryllium and californium-252. As a result, they discovered a transparent neutron shielding material that is little discolored by gamma ray irradiation using a specific epoxy resin composition, and completed the present invention. Summary of the Invention [Problem to be solved by the invention]
[0025] The present invention provides a transparent neutron shield that is excellent in radiation resistance and is solid at room temperature, and whose transparency is not impaired even when exposed to an environment containing high doses of gamma rays. [Means for solving the problem]
[0026] The gist of the present invention is a radiation-resistant transparent neutron shielding material made from a cured epoxy resin composition that has sufficiently high shielding performance against neutrons, exceeding that of water at room temperature, and has a light transmittance ratio of 0.2 or more at a wavelength of 550 nm before and after irradiation with 100 kGy of comma rays generated from cobalt-60. Effect of the Invention
[0027] The epoxy resin composition of the present invention has higher radiation resistance under high-dose-rate radiation exposure than existing transparent neutron shielding materials, and is an effective radiation shielding material with a small decrease in light transmittance due to radiation exposure. [Brief description of the drawings]
[0028] [Figure 1] FIG. 1 is a diagram showing a comparison between the measured and calculated values of attenuation of the dose of neutrons from an americium-beryllium neutron source for each shielding thickness for the radiation-resistant transparent neutron shielding material (Example 1). [Diagram 2] 1 is a graph comparing the attenuation of the dose due to neutrons from an americium-beryllium neutron source for each shielding thickness for the radiation-resistant transparent neutron shielding materials of Example 1 and Example 2. [Diagram 3] 1 is a photograph showing the coloration of the radiation-resistant transparent neutron shielding materials of Examples 1 and 2 after being irradiated with gamma rays from a cobalt-60 source at doses of 100 kGy and 1 MGy. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0029] The present invention will now be described in further detail. <Terminology explanation>
[0030] The term "transparent shielding material" as used in the present invention means that the presence or movement of an object can be observed through the shielding material.
[0031] According to JIST8141 sunshade protective equipment, Table JA.1-Usage standards are set for light transmission in various environments, from welding work to reflected light during outdoor work on snow. In addition, the light transmission rate of sunglasses for outdoor use is said to be 20-30%. <Epoxy resin raw material>
[0032] The epoxy resin used in the present invention is not particularly limited as long as it is a resin having an epoxy group. For example, aromatic epoxy resins having a skeleton such as bisphenol-A or bisphenol-F, and aliphatic epoxy resins having a skeleton such as alkylene glycol or cyclohexanediol, etc. are included. Among them, it is preferable to use an epoxy resin having an alicyclic skeleton.
[0033] The epoxy resin having an alicyclic skeleton is preferably selected from the group consisting of epoxy resins obtained by epoxidizing a cyclic olefin and epoxy resins obtained by hydrogenating an aromatic epoxy resin.
[0034] Examples of alicyclic epoxy resins obtained by epoxidizing cyclic olefins include 3,4-epoxycyclohexylmethyl-3',4'-epoxycyclohexanecarboxylate, 1,2-epoxy-vinylcyclohexene, bis(3,4-epoxycyclohexylmethyl)adipate, 1-epoxyethyl-3,4-epoxycyclohexane, limonene diepoxide, oligomeric alicyclic epoxy resins (Daicel Chemical Industries, Ltd. product names: Epolead GT300, Epolead GT400, EHPE-3150), etc. Among these, 3,4-epoxycyclohexylmethyl-3',4'-epoxycyclohexanecarboxylate is preferred, and by blending this alicyclic epoxy resin, the viscosity of the epoxy resin composition can be reduced and the workability can be improved.
[0035] Examples of epoxy resins obtained by hydrogenating aromatic epoxy resins include biphenol type epoxy resins such as bisphenol A type epoxy resins, bisphenol F type epoxy resins, 3,3',5,5'-tetramethyl-4,4'-biphenol type epoxy resins, and 4,4'-biphenol type epoxy resins, phenol novolac type epoxy resins, cresol novolac type epoxy resins, bisphenol A novolac type epoxy resins, naphthalene diol type epoxy resins, trisphenylol methane type epoxy resins, tetrakisphenylol ethane type epoxy resins, and phenol dicyclopentadiene novolac type epoxy resins, and the like, which are obtained by hydrogenating the aromatic rings of aromatic epoxy resins. Among these, hydrogenated epoxy resins obtained by hydrogenating the aromatic rings of bisphenol A type epoxy resins, bisphenol F type epoxy resins, and biphenol type epoxy resins are particularly preferred in that they can provide epoxy resins with a high hydrogenation rate.
[0036] The hydrogenation rate of the hydrogenated epoxy resin obtained by hydrogenating such an aromatic epoxy resin is preferably in the range of 90 to 100%, more preferably in the range of 95 to 100%. If the hydrogenation rate is less than 90%, it is not preferable because it absorbs light of short wavelengths, causing deterioration of the resin over time and yellowing. This hydrogenation rate can be measured by measuring the change in absorbance (wavelength: 275 nm) using a spectrophotometer.
[0037] The above-mentioned alicyclic epoxy resins may be used alone or in combination of two or more. <Hardening agent>
[0038] As the curing agent used in the present invention, it is preferable to use at least one of the group consisting of polyfunctional phenols, amine compounds, acid anhydride compounds, imidazole compounds, amide compounds, cationic polymerization initiators, and organic phosphines. Among them, acid anhydrides are preferable from the viewpoint of coloring. In addition, jER113 (registered trademark of Mitsubishi Chemical Corporation) can also be suitably used.
[0039] Examples of the acid anhydride include phthalic anhydride, tetrahydrophthalic anhydride, hexahydrophthalic anhydride, methyltetrahydrophthalic anhydride, methylhexahydrophthalic anhydride, methylnadic anhydride, trimellitic anhydride, dodecylsuccinic anhydride, chlorendic anhydride, trialkyltetrahydrophthalic anhydride, glycerol tris(anhydrotrimellitate), trialkyltetrahydrophthalic anhydride-maleic anhydride adduct, ethylene glycol bisanhydrotrimellitate, 5-(2,5-dioxotetrahydrofuryl)-3-methyl-3-cyclohexene-1,2-dicarboxylic anhydride, maleic anhydride, and condensates of maleic anhydride and unsaturated compounds. These may be used alone or in combination of two or more. Among them, alicyclic acid anhydrides are suitable for achieving high light transmittance. It is preferable to use the acid anhydride compound in the curing agent so that the equivalent ratio (acid anhydride groups of the acid anhydride compound in the curing agent relative to all epoxy groups in the epoxy compound-containing composition) is in the range of 0.6 to 1.0. Examples of alicyclic amine compounds include isoborondiamine, benzenediamine, 1,3-bisaminomethylcyclohexane, 4,4'-diaminocyclohexylmethane, and 3,3'-diamino-4,4'-diaminodicyclohexylmethane. These may be used alone or in combination of two or more. Among them, 3,3'-dimethyl-4,4'-diaminodicyclohexylmethane (trade name: BASF Larmin C200 or Mitsubishi Chemical jER Cure 113) has a long pot life and is suitable from the viewpoint of workability. <Accelerator>
[0040] It is intended to be used to increase the speed of the curing reaction. Specific examples include tertiary amines such as triethylamine and benzyldimethylamine, imidazoles such as 1-isobutyl-2-methylimidazole, 2-methylimidazole, 1-benzyl-2-methylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, and benzimidazole, organic phosphorus compounds such as tributylphosphine, methyldiphenylphosphine, triphenylphosphine, diphenylphosphine, phenylphosphine, and triphenyl phosphite, tetraphenylphosphonium tetraphenylborate, tetraphenylphosphonium tetra-p-tolylborate, tetra-n-butylphosphonium bromide, and tetra-n-butylphosphine. Examples of the latent curing accelerator include quaternary phosphonium salts such as sulfonium o,o-diethyl phosphorodithionate, tetraphenylphosphonium tetraphenylborate, tetraphenylphosphonium ethyltriphenylborate, and tetrabutylphosphonium tetrabutylborate, diazabicycloalkenes such as 1,8-diazabicyclo[5.4.0]undecene-7 and its organic acid salts, organometallic compounds such as zinc octylate, tin octylate, and aluminum acetylacetone complex, quaternary ammonium salts such as tetraethylammonium bromide and tetrabutylammonium bromide, boron compounds such as boron trifluoride and triphenylborate, and metal halide compounds such as zinc chloride and stannic chloride.Furthermore, latent curing accelerators such as high-melting point imidazole compounds, dicyandiamide, microcapsule-type latent accelerators in which the surface of phosphorus-based and phosphine-based accelerators is coated with a polymer, amine salt-type latent curing accelerators, Lewis acid salts, and Bronsted acid salts, which are high-temperature dissociation-type thermal cationic polymerization-type latent curing accelerators, can also be used. These curing accelerators can be used alone or in combination of two or more kinds. They are preferably used in an amount of 0.1 to 20 parts by weight per 100 parts by weight of the total epoxy compound components as solids. <Other additives>
[0041] In addition to the above-mentioned components, antioxidants, stabilizers, reactive or non-reactive diluents, plasticizers, release agents, flame retardants, pigments, colorants, fluorescent materials, etc. may be added to the curable epoxy resin composition of the present invention as necessary within the scope of the invention. In addition, fillers such as silica (fumed silica, colloidal silica, precipitated silica, etc.) and glass may be added for the purpose of improving various physical properties such as thermal expansion coefficient, hardness, and thixotropy. Glass can be used in any shape, including short fiber, long fiber, woven fabric, and nonwoven fabric. Types of glass that can be used include E glass, T glass, D glass, and NE glass. <Method of manufacturing molded body>
[0042] Air bubbles that cause a decrease in neutron shielding ability are trapped in the molded product, causing serious shielding defects and resulting in a molded product that cannot be used in practice. In view of this, the present invention solves this problem by taking a process in which the epoxy resin composition is degassed in advance when molding into a mold, the mixture is divided and poured intermittently into the mold, and the heat generated by curing is removed by cooling the outside of the mold while preventing the entrapment of bubbles at the bottom of the sprue of the mold.
[0043] Mixing of raw materials: Each compounding component is weighed and mixed. There are no particular restrictions on the mixer used for mixing, but it is preferable to use a mixer that can mix and degas at the same time. A typical example is a chemical mixer manufactured by Aikosha Seisakusho Co., Ltd.
[0044] Degassing: The resulting mixture is degassed using a dedicated degassing machine. Since the performance required for the molded product of the present invention is neutron shielding performance and light transmittance, it is essential to establish manufacturing technology that removes as many bubbles as possible from the molded product. The degassing machine may be a vacuum degassing device manufactured by Otsuka Seisakusho Co., Ltd. The degassing time is determined from the data on the rising tendency of reaction heat and the curing time for the selected mixture of epoxy resin and hardener. The time required for degassing is generally 1 to 120 minutes, and in practice it is preferably adjusted to 7 to 60 minutes.
[0045] Molding: There are no particular restrictions on the molding method, but a mold can be constructed according to the shape of the required parts, and a casting method can be used in which the degassed mixture is poured into the mold. After casting, the mold is left to stand at room temperature until it hardens sufficiently. The completion of hardening can be determined by measuring the temperature of the molded product. The time required for curing is generally 1 hour to 168 hours, and in practice it is preferably adjusted to 6 hours to 72 hours. <Evaluation of material shielding performance>
[0046] The energy of neutrons generated in these various industrial and medical procedures is generally around one million electron volts (MeV), and the neutron shielding performance of shielding materials can be evaluated using the energy spectrum of neutrons generated in nuclear fission reactions in nuclear reactors, etc.
[0047] Non-Patent Document 2 shows the effective dose of neutrons and secondary gamma rays per thickness of water when neutrons generated by spontaneous fission of Californium-252, a point isotropic source, penetrate through water.
[0048] To compare the neutron shielding performance of a neutron shielding material with that of water, the effective dose from neutrons and secondary gamma rays per thickness calculated under the same irradiation conditions as in Non-Patent Document 2 can be compared with the value for water described in the literature.
[0049] The effective dose due to neutrons and secondary gamma rays in the shielding material can be calculated by solving the Boltzmann equation for neutrons and secondary gamma rays using a combination of an appropriate neutron-gamma ray coupling cross section library and a discrete ordinates (Sn) calculation code or a Monte Carlo calculation code to obtain the neutron flux and secondary gamma ray flux, which can then be multiplied by a conversion factor to the effective dose.
[0050] The accuracy and validity of neutron dose calculations can be evaluated by irradiating a neutron beam that has passed through a collimator from a Californium-252 or Americium-241-Beryllium neutron source onto a flat test specimen made of the shielding material in question, measuring the effective neutron dose for each thickness of the shielding, and comparing this with the results of an analysis performed simulating an experimental system. The thickness of the shielding material can be adjusted by preparing several test specimens of the same thickness and stacking them appropriately.
[0051] Neutron dose can be measured using a dosimeter for neutrons with energies below those of fission neutrons, such as a commercially available neutron rem counter.
[0052] The change in transmittance due to radiation exposure can be measured as follows. To simulate high-dose irradiation of 100 kGy or 1 MGy, which corresponds to several years of use in a high-dose-rate radiation facility, accelerated testing can be performed using a facility capable of long-term irradiation at a high dose rate of approximately 10 kGy per hour, with irradiation for 10 or 100 hours.
[0053] Facilities capable of such long-term, high-dose-rate irradiation include irradiation facilities that use cobalt-60 sources.
[0054] The visible light transmittance of a sample that has been subjected to accelerated irradiation testing and a sample before the accelerated irradiation testing are measured, and the results are compared to evaluate the change in light transmittance due to radiation exposure.
[0055] A tint meter that measures the light transmittance of car window glass can be used as a transmittance measuring device, such as KETECH Industry Instrument Store's WTM-1100 or Satotec's visible light transmittance measuring device tint meter TM2000. EXAMPLES
[0056] The present invention will be explained in more detail below by showing examples, but the present invention is not limited to these examples.
[0057] Example 1 Hydrogenated bisphenol A type epoxy resin (YX8000 manufactured by Mitsubishi Chemical Corporation): 218 g, methyl hexahydrophthalic anhydride (RIKACID MH-700 manufactured by New Japan Chemical Co., Ltd.): 157 g, and methyl tributyl phosphonium dimethyl phosphate (PX-4MP manufactured by Nippon Chemical Industry Co., Ltd.): 2.2 g were weighed and mixed, and vacuum degassed for 30 minutes while stirring. The mixed liquid after stirring was poured into an acrylic mold (2 mm thick) with an inner dimension of 10 × 10 × 3 cm, and then held in a thermostatic chamber at an atmospheric temperature of 40 ° C. for 24 hours. The mixture was held in a thermostatic chamber at an atmospheric temperature of 80 ° C. for 1 hour, then heated to 90 ° C. and held for 8 hours. After further holding at 110 ° C. for 2 hours, it was removed from the mold, and the obtained molded body was held in a thermostatic chamber at an atmospheric temperature of 150 ° C. for 1.5 hours, and then naturally cooled in the chamber to obtain a test specimen (Example 1) for a shielding test of 10 × 10 × 3 cm. In addition, a test specimen measuring 5 x 5 x 1.1 cm was prepared and used for a radiation resistance test.
[0058] Example 2 Using the same procedure as in Example 1, 310 g of hydrogenated bisphenol A type epoxy resin (YX8000 manufactured by Mitsubishi Chemical Corporation) and 100 g of a curing agent 3,3'-dimethyl-4,4'-diaminodicyclohexylmethane (Jer113 manufactured by Mitsubishi Chemical Corporation) were mixed to obtain a test specimen for Example 2.
[0059] The effective dose transmission rate of water for Californium-252 neutrons shown in Table 10.1(2) of Non-Patent Document 2 is used as a comparative example for evaluating the shielding performance of the embodiment.
[0060] <Shielding performance evaluation of the embodiment> A neutron shielding experiment was carried out using five test specimens from Example 1, using an americium-beryllium neutron source. The attenuation of the neutron dose rate in the shielding obtained in this experiment is shown in Figure 1, in comparison with the attenuation obtained by experimental analysis using the continuous energy Monte Carlo method with the MCNP6.1 code. The actual measured values and the analytical values are in good agreement within the range of experimental error.
[0061] Using five test specimens of Example 2, a neutron shielding experiment was carried out using an americium-beryllium neutron source as in Example 1. The attenuation of the neutron dose rate in the shielding obtained in the experiment using Example 2 is shown in Figure 2 in comparison with the attenuation in Example 1. The neutron shielding performance of Example 1 and Example 2 is almost equivalent.
[0062] Based on these experimental results, the effective dose transmission (Ft) of the neutrons and secondary gamma rays in Example 1 and Example 2 was calculated from the attenuation of the neutron dose rate from Californium-252 and the effective dose rate of the secondary gamma rays calculated by continuous energy Monte Carlo calculation, and is shown in Table 1 in comparison with the comparative example.
[0063] [Table 1]
[0064] The effective dose transmission (Ft) at a thickness of 30 cm was 7.00% for water in the comparative example, whereas it was only 4.85% for Example 1, demonstrating high neutron shielding performance. <Evaluation of Radiation Resistance in Examples>
[0065] Test pieces of Example 1 and Example 2, both measuring 5×5×1.1 cm, were simultaneously irradiated for 10 hours and 100 hours using a cobalt-60 gamma ray source at a dose rate of 10 kGy / h to give doses of 100 kGy and 1 MGy.
[0066] Using a tint meter WTM-1100, the transmittance of visible light (wavelength 550 nm) was measured before and after irradiation for Example and Example 2. The measurement results are shown in Table 2, and photographs of the 5 x 5 x 1.1 cm thick samples of Example and Comparative Example 2 before and after irradiation are shown in Figure 3.
[0067] [Table 2]
[0068] Example 1 maintains a transmittance of 53.7% even after irradiation with 100 kGy, and the transmittance ratio with respect to the unirradiated state is 0.5 or more. Even after irradiation with 1 MGy, the transmittance remains at 26.0%, making it usable as a transparent material.
[0069] The transparent neutron shielding material of Example 2 had a transmittance of 22.6% after irradiation with 100 kGy, which is close to the limit of transmittance for use as a transparent material. After irradiation with 1 MGy, the transmittance was 6.4%, and it was hardly recognized as a transparent body. [Industrial Applicability]
[0070] From the above results, it can be seen that the neutron shielding material of the present invention, although being a solid, has better neutron shielding performance than water, which is the most common neutron shielding material, and is extremely less discolored by gamma ray irradiation compared to conventional transparent neutron shielding materials, contributing to radiation protection and more efficient work involving handling radioactive materials in various industries such as atomic energy and medical care.
Claims
1. A radiation-resistant transparent neutron shielding material comprising a cured epoxy resin composition that has shielding performance against neutrons produced by nuclear fission that exceeds that of water at room temperature, and has a transmittance ratio of 0.2 or more for light with a wavelength of 550 nm before and after irradiation with 100 kGy of gamma rays generated from cobalt-60, wherein the epoxy resin composition is an epoxy resin composition having an alicyclic skeleton, and further the epoxy resin composition contains a curing agent, and the curing agent is an acid anhydride.
2. 2. The radiation-resistant transparent neutron shielding material according to claim 1, wherein the alicyclic skeleton is an epoxy resin obtained by epoxidizing a cyclic olefin.
3. A radiation-resistant transparent neutron shielding material as described in claim 1, wherein the alicyclic skeleton is an epoxy resin obtained by hydrogenating an aromatic hydrocarbon.
4. 4. The radiation-resistant transparent neutron shielding material according to claim 1, wherein the acid anhydride has an alicyclic skeleton.
Citation Information
Patent Citations
Transparent neutron shield
JP1997026498A
Production method of transparent shielding material capable of shielding neutron
JP2001310928A
Composite plate having transparency superior in shielding effect for gamma ray and neutron beam
JP2003156591A
Radiation shielding article
JP2013088368A
Transparent neutron shielding material
WO2017213265A1